Incidence of mother‐to‐child transmission of hepatitis B in relation to maternal peripartum antiviral prophylaxis: A systematic review and meta‐analysis - Naijuan Yao; Shan Fu; Yuchao Wu; Zhen Tian; Yali Feng; Juan Li; Xufei Luo; Yuan Yang; Fanpu Ji; Yaolong Chen; Jinfeng Liu; Yingren Zhao; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Mother‐to‐child transmission (MTCT) of the hepatitis B virus (HBV) is a serious public health challenge. Estimating HBV MTCT incidence by region under different prophylaxis regimens is critical to understanding the regional disease burden and prioritizing interventions. This study aimed to calculate HBV MTCT incidence under different prophylaxis regimens globally and regionally and identify the HBV DNA threshold for maternal peripartum antiviral prophylaxis. Material and methods This review was registered in advance in PROSPERO (CRD 42019120567). We searched PubMed, Embase, China National Knowledge Infrastructure, ClinicalTrials.gov, and Cochrane Library databases for studies on MTCT in pregnant women with chronic HBV infection from their inception until June 13, 2022. MTCT was defined as hepatitis B surface antigen (HBsAg) or HBV DNA seropositivity in infants aged 6–12 months. We calculated the pooled HBV MTCT incidence using the DerSimonian‐Laird random‐effects model. Results Among 300 studies, 3402 of 63 293 infants had HBV due to MTCT. Without prophylaxis regimens, the pooled HBV MTCT incidence was 31.3%, ranging from 0.0% (95% confidence interval [CI] 0.0%–6.0%; European Region) to 46.1% (95% CI 29.7%–63.0%; Western Pacific Region). Following the introduction of the hepatitis B vaccine, the HBV MTCT incidence decreased from 82.9% to 15.9% in HBeAg‐positive women and from 10.3% to 2.3% in HBeAg‐negative women. Maternal peripartum antiviral treatment alongside infant immunoprophylaxis further decreased MTCT incidence to 0.3% (95% CI 0.1%–0.5%). Despite infant immunoprophylaxis, the incidences of MTCT at maternal HBV DNA levels of <2.30, 2.00–3.29, 3.00–4.29, 4.00–5.29, 5.00–6.29, 6.00–7.29 and ≥7.00 log10 IU/ml were 0.0% (95% CI 0.0%–0.0%), 0.0% (95% CI 0.0%–0.0%), 0.0% (95% CI 0.0%–0.5%), 0.6% (95% CI 0.0%–2.6%), 1.0% (95% CI 0.0%–3.1%), 4.3% (95% CI 1.8%–7.5%), and 9.6% (95% CI 7.0%–12.5%), respectively. Conclusions HBV MTCT incidence varies across regions. The Western Pacific Region bears the heaviest burden. Peripartum antiviral prophylaxis plus infant immunoprophylaxis is promising for interrupting HBV MTCT. Regarding the HBV DNA threshold for peripartum antiviral prophylaxis, maternal HBV DNA of 4.00 log10 IU/ml or greater seems justified.